التخارج بين الورثة أحكامه وصوره في الفقه الإسلامي - Muhammad Husni, Ahmad; Ahmad, Md. Yazid; Awang, Mohd. Ridzuan; Muda, Mohd. Zamro; Mohamed Said, Noor Lizza (Department of Shariah, Faculty of Islamic Studies, The National University of Malaysia, 2016)
فإنَّ المواريث في الإسلام من أهم فروع علم الشريعة، يحتاجها كل مسلم لمعرفة نصيبه في تركة مورثه ، وفق ما جاءت به الشريعة الإسلامية ، وهو يعد من المواضيع التي لم تنل حظها من الدراسات سواء عن طريق البحوث العلمية أو القوانين ويعد أيضاً من أدق مباحث علم الفرائض : التخارج بين الورثة والتصالح فيما بينهم على إخراج بعضهم من التركة مقابل شيءٍ يدفع له من التركة أو من غيرها ؛ وهو من المسائل التي يحتاجها الورثة دائمًا ؛ لقسمة التركات فيما بينهم ، وإخراج من لا يرغبون في بقائه معهم حين تكون التركات من العقارات ، والأشياء التي إذا قسمت على قواعد المواريث تضرر الورثة بذلك . وهذه المسألة من المسائل التي لم تنل ما تستحقُّه من البحث العلمي ؛ وإنما تطرقت إلى بعض من كتب في حساب الفرائض حديثًا إلى بيان بعض صورها وقسمتها ؛ لهذا رغبت في بحث هذه المسألة بحثًا علميًا فقهيًا . فنهجت الدراسة إلى المنهج الاستقرائي التحليلي لجمع آراء الفقهاء والباحثين وأدلتهم وحججهم حول الموضوع، والنصوص المتعلقة به محاولاً تحليلها تحليلاً فقهيا بما يناسب واقعنا المعاصر. ولذا يعد أولاً من العقود الناقلة للملكية وجب دراسته من خلال التركيز على أركانه وشروطه وأهم أحكامه التي يتميز عن بقية العقود الناقلة. ************************************************************************************** Inheritance is one of the most important branches of Islamic law, which every Muslim needs to know, to understand his share in the estate left behind by the deceased in accordance with the Islamic law; it is regarded as one of the subject that has not been adequately researched on, in terms of both academic and law. Another most important part of inheritance in Islamic law is the issue of reconciliation between heirs on estate of inheritance to remove one or some of them from the division of the estate in exchange of something paid to him or them; it is of the issues needed by the heirs at all time to divide the estate between them, and to remove the one they do not need to remain with them when the subject matter is real estate, and things that may be affected if are divided based on the principles of inheritance. This issue is of the issues that do not get their adequate share of research; and those who wrote on inheritance among the contemporary scholars only discussed some of its forms and division; for this I wish to discuss this issue from the jurisprudential point of issue. This study adopts inductive and analytical approach to gather the views of scholars and researchers and their evidence and arguments on the matter, and texts related to it and to try to analyze them to suit our contemporary reality. So, it is considered contracts that move ownership that must be studied by focusing on the pillars and conditions and the most important provisions which are distinct from the rest of contracts that move ownership. ************************************************************************************** Pewarisan merupakan satu cabang penting dalam undang-undang Islam, yang setiap antara kita perlu tahu dan faham mengenai bahagiannya dalam harta yang ditinggalkan oleh si mati berdasarkan undang-undang Islam; ia dianggap sebagai salah satu perkara yang belum dikaji secara menyeluruh, dari segi akademik dan undang-undang. Satu lagi perkara penting berkenaan pewarisan dalam undang-undang Islam adalah mengenai isu perdamaian di antara ahli waris berkenaan harta pusaka. Ia adalah antara isu yang diperlukan oleh ahli waris setiap kali membahagikan harta dalam kalangan mereka, dan untuk mengeluarkan seseorang yang mereka tidak perlukan untuk kekal bersama mereka apabila perkara tersebut melibatkan hartanah, dan sesuatu yang boleh memberi kesan sekiranya dibahagikan berdasarkan prinsipprinsip pembahagian harta pusaka. Kajian ini menggunakan pendekatan induktif dan analisis bagi mengumpul pandangan ulama dan penyelidik serta bukti dan hujah mereka mengenai perkara itu, dan ayat-ayat yang berkaitan dengannya seterusnya cuba untuk menganalisis untuk memenuhi realiti kontemporari semasa. Oleh itu, ia dianggap sebagai sebuah kontrak yang memindahkan pemilikan yang perlu dikaji dengan memberi tumpuan kepada rukun dan syarat serta peruntukan yang paling penting yang membezakannya dengan kontrak pindah milik yang lain.